Molecular Characteristics of Human Adenovirus Type 3 Circulating in Parts of China During 2014–2018 - Duan, Yali; Xu, Baoping; Li, Changchong; Bao, Yixiao; An, Shuhua; Zhou, Yunlian; Chen, Aihuan; Deng, Li; Ning, Limin; Zhu, Yun; Wang, Wei; Zhang, Meng; et al. (Frontiers in Microbiology, 2021)
Human adenoviruses (HAdVs) are important pathogens causing respiratory infections; 3.5%–11% of childhood community acquired pneumonia is associated with HAdV infection. Human adenovirus type 3 (HAdV-3)，leading to severe morbidity and mortality, is one of the most prevalent genotype among adenoviruses responsible for acute respiratory infections (ARI) in children in China. To identify the genetic variation of HAdV-3 in children with ARI in China, a molecular epidemiological study was conducted. A total of 54 HAdV-3 isolated strains were obtained from children with ARI in Beijing, Wenzhou, Shanghai, Shijiazhuang, Hangzhou, Guangzhou, and Changchun from 2014–2018. Thirty-two strains of which were selected for whole genome sequencing, while the hexon, penton base and fiber genes were sequenced for remaining strains. Bioinformatics analysis was performed on the obtained sequences. The phylogenetic analyses based on whole genome sequences, major capsid protein genes (hexon, penton base and fiber) and early genes (E1, E2, E3, and E4) showed that the HAdV-3 strains obtained in this study always clustered together with the reference strains from Chinese mainland. While the HAdV-3 prototype strain formed a cluster independently. Comparing with prototype strain, all strains possessed 9 amino acid (AA) substitutions at neutralization antigenic epitopes of hexon. The homology models of hexon protein of HAdV-3 prototype and strain BJ20160214 showed that there was no evident structural change at the amino acid mutation sites. Two AA substitutions were found at the Arg-Gly-Asp (RGD) loop and hypervariable region 1 (HVR1) region of the penton. A distinct AA insertion (20P) in the highly conserved PPPSY motif of the penton that had never been reported before was observed. Recombination analysis indicated that partial regions of protein IIIa precursor, penton base and protein VII precursor genes among all HAdV-3 strains in this study were from HAdV-7. This study showed that the genomes of the HAdV-3 strains in China were highly homologous. Some AA mutations were found at antigenic sites, however, the significance needs further study. Our data demonstrated the molecular characteristics of HAdV-3 circulating in China and was highly beneficial for further epidemiological exploration and the development of vaccines and drugs against HAdV-3.